Application of water safety planning to improve drinking water safety in an Arctic community – a case study in Cambridge Bay, Nunavut - Caroline Duncan; Elan Chalmers; Stephanie Gora (International Journal of Circumpolar Health)
Water safety planning is a risk management approach that accounts for quantitative and qualitative drinking water hazards and includes ongoing input from stakeholders. This approach has been applied in jurisdictions across the world including Canada. Rural and remote communities in Canada, impacted by water safety, stand to benefit most from holistic approaches to water safety risk management such as water safety planning. Unfortunately, these communities typically have limited resources to engage in this approach. Additionally, most remote communities rely on truck and cistern water systems, which have less understood hazards than communities in Canada with piped service. In this study, we report the results of an initial water safety planning case study in Cambridge Bay, Nunavut. We identified numerous water quality hazards including disinfection byproducts in trucks, manganese in the source water, and copper in tap water, as well as operational challenges that increase the risk of water emergencies in the community. We conclude that water safety planning has the potential to substantially improve water safety in Nunavut but current information gaps as well as complex stakeholder interactions are likely to hinder top-down attempts. A dynamic and inclusive approach is recommended that incorporates a targeted exploration of water safety hazards.